High-barrier polyamide master batch and preparation method thereof
By constructing supramolecular ionic polymers and nano-layered double hydroxides, combining carrier resins and rheology additives, high-barrier polyamide masterbatches are prepared, which solves the problem of insufficient barrier performance of MXD6 materials and achieves efficient gas barriers and Good mechanical properties.
Patent Information
- Application Number
- CN202310856889.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
AI Technical Summary
The barrier properties of existing MXD6 materials cannot meet the increasing requirements, and it is difficult to effectively peel off the montmorillonite in the two-dimensional sheet-like structure, affecting its barrier and mechanical properties.
The supramolecular ion polymer is constructed by reaction of heteropoly acid anions and multifunctional imidazole cations to form supramolecular ion polymer stripped nanomontmorillonite and nanolayered double hydroxide, combined with carrier resin, hyperbranched rheology additive and joint Coupling agent, high-barrier polyamide masterbatch is prepared by melt granulation by twin screw extruder.
The polyamide masterbatch with high dispersion and high gas barrier properties is achieved, maintaining the processing and mechanical properties of the MXD6 matrix, and is suitable for use in high temperature and high humidity environments.
Smart Images

Figure CN119307091A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high-barrier polyamide masterbatch and a preparation method thereof. Background Art
[0002] Poly(m-phenylenediamine adipamide), referred to as MXD6 in English, has higher mechanical strength and modulus than other engineering plastics, and is also a special high-barrier polyamide material. Although the barrier property of MXD6 is slightly worse than that of PVDC and EVOH, it can preserve the flavor of food, has a lasting barrier property for hydrocarbon gases, O2 and CO2, and its barrier property is not affected by temperature and humidity, which is especially suitable for use in high temperature and humid occasions. Therefore, with the increasingly high requirements for barrier properties and diversified forms today, MXD6 has become one of the new varieties of polymer materials that attract attention.
[0003] Although MXD6 itself has excellent barrier properties, its performance cannot meet the increasingly high barrier requirements, so its barrier properties must be improved. Two-dimensional lamellar structures are often used to prepare nanocomposites to improve the barrier properties of substrates, and related research is very rich. The dispersion of the lamellar layers in the polymer matrix is the key to the barrier performance. Otherwise, not only the barrier performance is poor, but also the mechanical properties may be damaged. At present, there are many two-dimensional lamellar structures, among which montmorillonite (MMT) is the most common and the most studied system. The preparation methods of MMT / MXD6 mainly include intercalation composite method, in-situ composite method, etc. Among them, the intercalation composite method does not affect the polymerization process and is more widely used. Its main process is: inserting organic small molecules or macromolecules between the lamellar layers of rigid MMT, and then using melt intercalation or polymerization to expand the distance between adjacent lamellar layers, or dissociate them and evenly disperse them in the polymer matrix. Currently, organic small molecules suitable for intercalation are often not heat-resistant and cannot meet the processing requirements of MXD6. There are few polymer macromolecules to choose from, and it is also difficult to insert them into the MMT layer to achieve the stripping effect. Therefore, it is urgent to find a better solution.
[0004] By reacting heteropolyacid anions and multifunctional imidazole cations to construct supramolecular ionic polymer exfoliation nanosheets between MMT or LDH layers, the problem of difficult sheet exfoliation can be solved. In addition, the supramolecular ionic polymer structure formed by the reaction of heteropolyacid anions and multifunctional imidazole cations has good thermal stability and good compatibility with MXD6. On the one hand, it is expected to prepare an easily dispersed high-barrier polyamide masterbatch for the preparation of high-barrier films; on the other hand, adding this polyamide masterbatch can have no or little damage to the various properties of MXD6 such as mechanical properties, processing properties, thermal stability, etc., and it is also convenient for transportation and processing. Summary of the invention
[0005] In view of the above-mentioned defects of the prior art, an object of the present invention is to provide a high barrier polyamide masterbatch.
[0006] To solve the above problems, the technical solution of the present invention is: a high-barrier polyamide masterbatch, which is a mixture of supramolecular ionic polymer exfoliated nano-montmorillonite, supramolecular ionic polymer exfoliated nano-layered double hydroxide, carrier resin, hyperbranched rheological additive, antioxidant and coupling agent. Every 100 weight parts of the high-barrier polyamide masterbatch contains 30-45 parts of supramolecular ionic polymer exfoliated nano-montmorillonite / supramolecular ionic polymer exfoliated nano-layered double hydroxide, 50-65 parts of carrier resin, 0.3-1.5 parts of hyperbranched rheological additive, 0.3-2 parts of antioxidant and 0.5-1.5 parts of coupling agent.
[0007] Furthermore, the weight ratio of the supramolecular ionic polymer exfoliated nano-montmorillonite to the supramolecular ionic polymer exfoliated nano-layered double hydroxide is 4 / 1 to 1 / 2.
[0008] Furthermore, the carrier resin is one of MXD6 and PA6;
[0009] The hyperbranched rheological additive is one of carboxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyphosphate, and phosphate-terminated hyperbranched polyphosphate;
[0010] The antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxy)phenylpropionic acid]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid octadecyl alcohol ester, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, and bis(octadecyl)pentaerythritol diphosphite;
[0011] The coupling agent is one of triglycidyl isocyanurate and ADR4468.
[0012] Furthermore, the supramolecular ionic polymer exfoliated nano-montmorillonite is an exfoliated organic MMT containing supramolecular ionic polymers composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions between the layers.
[0013] Furthermore, the chemical structural formula of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them.
[0014] Furthermore, the chemical structural formula of the multifunctional imidazolium cation is:
[0015]
[0016] Furthermore, the supramolecular ionic polymer exfoliated nano-layered double hydroxide is an exfoliated organic LDH of supramolecular ionic polymers composed of sulfonic acid anions, diimidazole cations and heteropolyacid anions between the layers.
[0017] Furthermore, the chemical structural formula of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them.
[0018] Furthermore, the chemical structural formula of the dibasic imidazolium cation is:
[0019]
[0020] The present invention also provides the above-mentioned high-barrier polyamide masterbatch and a preparation method thereof, comprising mixing supramolecular ionic polymer exfoliated nano-montmorillonite, supramolecular ionic polymer exfoliated nano-layered double hydroxide, carrier resin, antioxidant and hyperbranched rheological additive in proportion, adding the mixture into a kneader and stirring evenly, drying the mixture at 60-100° C. in vacuum for 1-6 hours to obtain a coarse material; crushing the coarse material and mixing it evenly with a coupling agent, melting, extruding and granulating the mixture through a twin-screw extruder to obtain a finished masterbatch.
[0021] The beneficial effects of the present invention are:
[0022] A high-barrier polyamide masterbatch is prepared by combining and optimizing supramolecular ion polymer stripping nano-montmorillonite / supramolecular ion polymer stripping nano-layered double hydroxide, hyperbranched rheological additives and chain extenders, and melt granulating with a twin-screw extruder. The high-barrier polyamide masterbatch prepared by the present invention has good dispersibility and can be directly added to the MXD6 matrix in proportion to achieve high gas barrier performance, and can maintain the good processing performance and mechanical properties of the MXD6 matrix. The method for preparing the high-barrier polyamide masterbatch provided by the present invention is simple to operate and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The structural formula of supramolecular ion polymer exfoliated nano-montmorillonite (C-MMT);
[0024] Figure 2 This is the structural formula of supramolecular ionic polymer exfoliated nanolayered double hydroxide (C-LDH). DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with embodiments:
[0026] A high barrier polyamide masterbatch is a mixture of supramolecular ion polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ion polymer exfoliated nano-layered double hydroxide (C-LDH), carrier resin, hyperbranched rheological additive, antioxidant and coupling agent.
[0027] The ratio of supramolecular ion polymer exfoliated nano-montmorillonite (C-MMT) / supramolecular ion polymer exfoliated nano-layered double hydroxide (C-LDH) is 4 / 1 to 1 / 2 by weight.
[0028] The carrier resin is one of MXD6 and PA6;
[0029] The hyperbranched rheological additive is one of carboxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyphosphate, and phosphate-terminated hyperbranched polyphosphate;
[0030] The antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxy)phenylpropionic acid]pentaerythritol ester (antioxidant 1010), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid octadecyl alcohol ester (antioxidant 1076), tris(2,4-di-tert-butylphenyl)phosphite (antioxidant 168), bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite (antioxidant 626), and bis(octadecyl)pentaerythritol diphosphite (antioxidant 618);
[0031] The coupling agent is one of triglycidyl isocyanurate and ADR4468.
[0032] Supramolecular ionic polymer exfoliated nanomontmorillonite (C-MMT) is an exfoliated organic MMT composed of supramolecular ionic polymers composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions between the layers. The chemical structure of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- The chemical structure of the multifunctional imidazolium cation is:
[0033]
[0034] Supramolecular ionic polymer exfoliated nano-layered double hydroxide (C-LDH) is an exfoliated organic LDH composed of supramolecular ionic polymers containing sulfonic acid anions, diimidazolium cations and heteropolyacid anions between the layers. The chemical structure of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them. The chemical structural formula of the diimidazolium cation is:
[0035]
[0036] Example 1
[0037] 400g C-MMT / C-LDH (weight ratio 4 / 1), 577g MXD6, 3g antioxidant 1010, and 10g terminal carboxyl hyperbranched polyester were added to a kneader and stirred to mix evenly. After the material was taken out, it was dried at 60°C in vacuum for 6h, crushed, and mixed evenly with 8g coupling agent TGIC. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g of a high barrier polyamide masterbatch finished product.
[0038] Example 2
[0039] 450g C-MMT / C-LDH (weight ratio 3 / 1), 532g MXD6, 5g antioxidant 1076, and 5g terminal hydroxyl hyperbranched polyester were added into a kneader and stirred to mix evenly. After the material was taken out, it was dried at 70°C in vacuum for 5h, crushed, and mixed evenly with 8g coupling agent ADR4468. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g high barrier polyamide masterbatch finished product.
[0040] Example 3
[0041] 300g C-MMT / C-LDH (weight ratio 2 / 1), 560g PA6, 8g antioxidant 168, and 20g terminal hydroxyl hyperbranched polyphosphate were added to a kneader and stirred to mix evenly. After the material was taken out, it was dried at 80°C in vacuum for 4h, crushed, and mixed evenly with 12g coupling agent ADR4468. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g of a high barrier polyamide masterbatch finished product.
[0042] Example 4
[0043] 350g C-MMT / C-LDH (weight ratio 1 / 1), 635g MXD6, 5g antioxidant 626, and 10g terminal phosphate hyperbranched polyphosphate were added to a kneader and stirred to mix evenly. After the material was taken out, it was dried at 90°C in vacuum for 2h, crushed, and mixed evenly with 6g coupling agent ADR4468. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g of a high barrier polyamide masterbatch finished product.
[0044] Example 5
[0045] 400g C-MMT / C-LDH (weight ratio 1 / 2), 570g MXD6, 10g antioxidant 618, and 10g terminal carboxyl hyperbranched polyester were added to a kneader and stirred to mix evenly. After the material was taken out, it was dried at 100°C in vacuum for 1h, crushed, and mixed evenly with 10g coupling agent ADR4468. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g of a high barrier polyamide masterbatch finished product.
[0046] Example 6
[0047] 450C-MMT / C-LDH (weight ratio 4 / 1), 500g PA6, 20g antioxidant 618, and 15g terminal hydroxyl hyperbranched polyester were added into a kneader and stirred to mix evenly. After the material was taken out, it was dried at 90°C in vacuum for 1h, crushed, and mixed evenly with 15g coupling agent TGIC. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g high barrier polyamide masterbatch finished product.
[0048] Example 7
[0049] 300g C-MMT / C-LDH (weight ratio 3 / 1), 640g MXD6, 8g antioxidant 1010 and 4g antioxidant 168, and 30g terminal hydroxyl hyperbranched polyphosphate were added into a kneader and stirred to mix evenly. After the material was taken out, it was dried at 80°C in vacuum for 3h, crushed, and mixed evenly with 18g coupling agent TGIC. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g high barrier polyamide masterbatch finished product.
[0050] Example 8
[0051] 350g C-MMT / C-LDH (weight ratio 2 / 1), 590g PA6, 8g antioxidant 1010 and 7g antioxidant 618, and 25g terminal phosphate hyperbranched polyphosphate were added to a kneader and stirred to mix evenly. After the material was taken out, it was dried at 70°C in vacuum for 4h, crushed, and mixed evenly with 20g coupling agent TGIC. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g high barrier polyamide masterbatch finished product.
[0052] Example 9
[0053] 450C-MMT / C-LDH (weight ratio 4 / 1), 500g MXD6, 10g antioxidant 1010 and 10g antioxidant 168, and 15g terminal hydroxyl hyperbranched polyester were added into a kneader and stirred to mix evenly. After the material was taken out, it was dried at 90°C in vacuum for 1h, crushed, and mixed evenly with 15g coupling agent TGIC. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g high barrier polyamide masterbatch finished product.
[0054] Example 10
[0055] 450C-MMT / C-LDH (weight ratio 3 / 1), 500g MXD6, 10g antioxidant 1076 and 10g antioxidant 168, and 15g terminal hydroxyl hyperbranched polyester were added into a kneader and stirred to mix evenly. After the material was taken out, it was dried at 90°C in vacuum for 1h, crushed, and mixed evenly with 15g coupling agent TGIC. Then, it was melted, extruded, and granulated through a twin-screw extruder to obtain 1000g high barrier polyamide masterbatch finished product.
[0056] The high barrier polyamide masterbatch prepared in the above embodiments was added to the MXD6 matrix in different proportions, and the measured properties were as follows:
[0057] Table 1. Performance comparison of various embodiments
[0058]
[0059] It can be seen from the data in Table 1 that after the high barrier polyamide masterbatch prepared in Examples 1 to 10 is added to the MXD6 matrix, its barrier performance is greatly improved.
Claims
1. A high barrier polyamide masterbatch, characterized in that: It is a mixture of supramolecular ionic polymer exfoliated nano-montmorillonite, supramolecular ionic polymer exfoliated nano-layered double hydroxide, carrier resin, hyperbranched rheological additive, antioxidant and coupling agent. Every 100 parts by weight of the high-barrier polyamide masterbatch contains 30-45 parts of supramolecular ionic polymer exfoliated nano-montmorillonite / supramolecular ionic polymer exfoliated nano-layered double hydroxide, 50-65 parts of carrier resin, 0.3-1.5 parts of hyperbranched rheological additive, 0.3-2 parts of antioxidant and 0.5-1.5 parts of coupling agent.
2. The high barrier polyamide masterbatch according to claim 1, characterized in that: The weight ratio of the supramolecular ionic polymer stripped nano-montmorillonite to the supramolecular ionic polymer stripped nano-layered double hydroxide is 4 / 1 to 1 / 2.
3. The high barrier polyamide masterbatch according to claim 1, characterized in that: The carrier resin is one of MXD6 and PA6; The hyperbranched rheological additive is one of carboxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyphosphate, and phosphate-terminated hyperbranched polyphosphate; The antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxy)phenylpropionic acid]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid octadecyl alcohol ester, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, and bis(octadecyl)pentaerythritol diphosphite; The coupling agent is one of triglycidyl isocyanurate and ADR4468.
4. The high barrier polyamide masterbatch according to claim 1, characterized in that: The supramolecular ionic polymer exfoliated nano-montmorillonite is an exfoliated organic MMT containing supramolecular ionic polymers composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions between the layers.
5. The high barrier polyamide masterbatch according to claim 4, characterized in that: The chemical structural formula of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3 -、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them.
6. The high barrier polyamide masterbatch according to claim 4, characterized in that: The chemical structural formula of the multifunctional imidazolium cation is:
7. The high barrier polyamide masterbatch according to claim 4, characterized in that: The supramolecular ionic polymer exfoliated nano-layered double hydroxide is an exfoliated organic LDH composed of supramolecular ionic polymers containing sulfonic acid anions, diimidazole cations and heteropolyacid anions between the layers.
8. The high barrier polyamide masterbatch according to claim 7, characterized in that: The chemical structural formula of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them.
9. The high barrier polyamide masterbatch according to claim 7, characterized in that the chemical structural formula of the diimidazolium cation is:
10. The method for preparing a high barrier polyamide masterbatch according to claim 1, characterized in that: Supramolecular ionic polymer exfoliated nano-montmorillonite, supramolecular ionic polymer exfoliated nano-layered double hydroxide, carrier resin, antioxidant and hyperbranched rheological additive are mixed in proportion, added into a kneader, stirred evenly, and dried at 60-100° C. in vacuum for 1-6 hours to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, melted, extruded and granulated through a twin-screw extruder to obtain a masterbatch product.